PENGARUH LINGKUNGAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI DINAS PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN SITUBONDO - Ningsih, Busri Wahyu; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Competing effectively in a competitive business environment, an organization requires solid and sustainable resources. These resources include various things, such as sufficient financial capital, reliable infrastructure, up-to-date technology, as well as competent and skilled human resources. The aim of this research is to analyze and test the influence of organizational culture, work environment, compensation and organizational culture on performance. With Job Satisfaction as an intervening variable in the Situbondo Regency Tourism, Youth and Sports Office. This research is explanatory research. The population in this study were employees of the Tourism, Youth and Sports Department. The sampling technique uses a saturated sample technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). Hypothesis test results of direct influence using the Smart PLS 3.0 application, Work environment has a significant positive effect on job satisfaction, Compensation has a negative and insignificant effect on job satisfaction, Organizational culture has a significant positive effect on job satisfaction, Work environment has a negative and insignificant effect on Performance, Compensation has a negative effect not significant on Performance, Organizational culture has a significant positive effect on Performance, Job satisfaction has a significant positive effect on Performance, Work Environment has a significant positive effect on Performance through Job Satisfaction, Compensation has a negative and insignificant effect on Performance through Job Satisfaction, Organizational culture has a significant effect positive impact on performance through job satisfaction.